Liquidity Management and Returns of Shareholders in Quoted Banks of Nigeria - Kan, David (International Journal of Finance and Accounting, 2016)
Purpose: This study access liquidity management with the aim of determining its effect on returns of shareholders. Ex-post factor design was adopted. Data on ROE, ROA, Log of Sales and EPS were collected from the selected Banks financial statement and Nigerian Stock Exchange statistical bulletin. ROA and ROE proxied performance while EPS proxied returns to shareholders. Liquidity stood for liquidity management. Purpose: The study covered a period of 2000-2014. Unit root was used to test the data for stationarity issue and where there was unit root problem, the data were differenced. Auto-regressive method was also applied to solve auto-regression issues. Linear regression and Pearson correlation were used to test the hypotheses. Results: The result showed that there is no significant relationship between liquidity management and Nigerian quoted Banks performance as well as return of Shareholders. Recommendation; the researcher therefore recommended that policies should be put in place to reduce the cost of loan and encourage investment in Nigeria.